2005
DOI: 10.1097/01.bsd.0000133494.70621.2e
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment with Instrumentation for Severely Destructive Spondyloarthropathy of Cervical Spine

Abstract: Nine patients with severely destructive spondyloarthropathy and marked neurologic deficits associated with dialysis-related amyloidosis underwent posterior decompression and fusion by means of instrumentation at our institute. All patients showed segmental kyphosis, six patients vertebral ankylosis, and eight patients spondylolisthesis. Spondylolisthesis at two levels was noted in three patients. Of the 11 levels of spondylolisthesis in all, 9 were proximally adjacent and 2 were distally adjacent to vertebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Albumi et al believe that cervical spine DSA often requires circumferential reconstructive surgery, because affected patients typically have both the anterior columns and the facet joints compromised [4]. In contrast, Yuzawa et al suggest that anterior long-span surgery may be too invasive in hemodialysis patients, whereas posterior decompression and fusion may be a reasonable, effective strategy for severe hemodialysis-associated cervical spondyloarthropathy with neurologic deficits [8]. On the other hand, Nair et al reported two cases managed with anterior approach due to anterior compression, with one of the two requiring supplemental posterior fixation because of hardware failure and pseudarthrosis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Albumi et al believe that cervical spine DSA often requires circumferential reconstructive surgery, because affected patients typically have both the anterior columns and the facet joints compromised [4]. In contrast, Yuzawa et al suggest that anterior long-span surgery may be too invasive in hemodialysis patients, whereas posterior decompression and fusion may be a reasonable, effective strategy for severe hemodialysis-associated cervical spondyloarthropathy with neurologic deficits [8]. On the other hand, Nair et al reported two cases managed with anterior approach due to anterior compression, with one of the two requiring supplemental posterior fixation because of hardware failure and pseudarthrosis [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis reported by Tian et al, the accuracy of pedicle screw insertion by CT navigation (90.76%) was significantly improved compared to the two-dimensional imaging system (85.48%) [16]. Our institution employs a CT-based navigation system for the cervical pedicle screw insertion [9][10][11][12]. The result of this paper was that the percentage of major perforations were 4.4%, total perforation rates were 17.9% for all cervical pedicle screws.…”
Section: Discussionmentioning
confidence: 99%
“…However, cervical pedicle screw insertion is technically demanding because of the narrow pedicle diameter and the risk of serious neurovascular complications including vertebral artery tear, spinal cord injury, and nerve root injury [7]. To achieve more accurate and safe pedicle screw insertion, navigation by two-dimensional imaging system or CT has been employed in recent years [9][10][11][12]. However, CPS insertion from C3 to C6 is technically demanding.…”
Section: Introductionmentioning
confidence: 99%
“…Among the previous reports of perforation rates of cervical pedicle screw by disease, the perforation rates for RA, DSA, and spinal trauma were 0-22% [9,10], 6.1% [11], and 3.9-9.2% [12], respectively. Insertion methods employed in these reports included CT-based navigation and twodimensional imaging systems.…”
Section: Discussionmentioning
confidence: 99%
“…A difference in CPS perforation rate according to bone quality or morphology of pedicle is to be expected; however, whether there are differences in CPS perforation rate due to variation in bone quality because of osteoporosis or osteosclerotic pedicle, or by morphology or size of pedicles, is not clearly understood. In addition, differences in CPS perforation rates according to disease may exist; however, although CPS perforation rates for rheumatoid arthritis (RA), DSA, and trauma treatment by various procedures have been *Address correspondence to this author at the Department of Orthopaedic Surgery, Shinshu University, School of Medicine, 3-1-1 Asahi, MatsumotoCity, Nagano, 390-8621, Japan; Tel: 81-263-37-2659; Fax: 81-263-35-8844; E-mail: jtaka@shinshu-u.ac.jp reported [8][9][10][11][12], there have been no reports on CPS perforation rates by disease. The purpose of this study is to evaluate the perforation rates of cervical pedicle screw insertion using CT-based navigation system by disease and vertebral level (from C2 to C7).…”
Section: Introductionmentioning
confidence: 99%